Did court stop college from enforcing suspension?. Issue 6 (7th September 2020) - Lyerly, Eric
Abstract : The plaintiff, a senior at Vassar College, was the captain of the school's soccer team. In May 2019, a female classmate reported to the Title IX coordinator that the plaintiff attempted to coerce her into a sexual encounter after a party they both attended. She also claimed he had engaged in nonconsensual sexual touching of her body in violation of the school's Sexual Misconduct Policy.